2008
DOI: 10.1113/jphysiol.2007.149120
|View full text |Cite
|
Sign up to set email alerts
|

Slow‐ and fast‐twitch rat hind limb skeletal muscle phenotypes 8 months after spinal cord transection and olfactory ensheathing glia transplantation

Abstract: Paralysed skeletal muscle of rats with spinal cord injury (SCI) undergoes atrophy and a switch in gene expression pattern which leads to faster, more fatigable phenotypes. Olfactory ensheathing glia (OEG) transplants have been reported to promote axonal regeneration and to restore sensory-motor function in animals with SCI. We hypothesized that OEG transplants could attenuate skeletal muscle phenotypic deterioration and that this effect could underlie the functional recovery observed in behavioural tests. A va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…The extensor digitorum longus (EDL) and soleus (SOL) muscles have been widely used as representative fast and slow muscles, respectively [27,28,29,30,31]. They both are hind limb muscles and very small in size (each contains about 1000 myofibers) in mouse, thus allowing for unbiased analysis of myofiber composition and gene expression at the whole muscle level [23].…”
Section: Resultsmentioning
confidence: 99%
“…The extensor digitorum longus (EDL) and soleus (SOL) muscles have been widely used as representative fast and slow muscles, respectively [27,28,29,30,31]. They both are hind limb muscles and very small in size (each contains about 1000 myofibers) in mouse, thus allowing for unbiased analysis of myofiber composition and gene expression at the whole muscle level [23].…”
Section: Resultsmentioning
confidence: 99%
“…23 It was found that prolonged IGF-I treatment in mdx mice can induce muscle fibers from a fast-twitch phenotype toward the slow-twitch phenotype without a change in fiber cross areas. 22 Compared with fasttwitch muscle, slow-twitch muscle fibers are rich in mitochondria, 24 have higher oxidative capacities, 25 and therefore use ATP in a more efficient way and produce less ROS, which would cause less or no damage to muscle cells. Our finding that IGF-I is able to prevent muscle cell from H 2 O 2 -induced cell death and recover cell viability may offer a rational explanation for IGF-I conferring protection on dystrophic muscle from contraction-induced damage.…”
Section: Discussionmentioning
confidence: 99%
“…The paralyzed skeletal muscle of rats with spinal cord injury (SCI) undergoes atrophy that was accompanied by spontaneous locomotor function recovery [21]. However, the underlying mechanism for this phenomenon after SCI is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, EGF-induced upregulation of eIF-5A stimulated corneal epithelial cell proliferation via the PI3K/Akt signaling pathway [21]. According to KEGG database, the PI3K/ Akt signaling pathway regulates fundamental cellular functions such as transcription, translation, proliferation, growth, survival, and cell cycle.…”
mentioning
confidence: 99%